Optimization technique for time domain applications - (:unkn) unknown (IEEE, Piscataway, NJ, United States, 1994)
An optimization technique for time domain applications is presented. The technique uses a modification of Powell's algorithm to obtain the best non-linear least squares fit between the simulated and experimental time domain responses. This set is said to be an optimal solution for the optimization process. From the optimal solution, the material properties of the stripline under test are obtained.